Thermal stability of the Mobil Five type metallosilicate molecular sieves - an in situ high, temperature X-ray diffraction study - Bhange, Deu S.; Ramaswamy, Veda (Materials Research Bulletin, 2007)
We have carried out in situ high temperature X-ray diffraction (HTXRD) studies of silicalite-1 (S-1) and metallosilicate molecular sieves containing iron, titanium and zirconium having Mobil Five (MFI) structure (iron silicalite-1 (FeS-1), titanium silicalite-1 (TS-1) and zirconium silicalite-1 (ZrS-1), respectively) in order to study the thermal stability of these materials. Isomorphous substitution of Si4+ by metal atoms is confirmed by the expansion of unit cell volume by X-ray diffraction (XRD) and the presence of Si-O-M stretching band at similar to 960 cm(-1) by Fourier transform infrared (FTIR) spectroscopy. Appearance of cristobalite phase is seen at 1023 and 1173 K in S-1 and FeS-1 samples. While the samples S-1 and FeS-1 decompose completely to cristobalite at 1173 and 1323 K, respectively, the other two samples are thermally stable upto 1623 K. This transformation is irreversible. Although all materials show a negative lattice thermal expansion, their lattice thermal expansion coefficients vary. The thermal expansion behavior in all samples is anisotropic with relative strength of contraction along `a' axes is more than along `b' and V axes in S- 1, TS-1, ZrS-1 and vice versa in FeS-1. Lattice thermal expansion coefficients (alpha(v)) in the temperature range 298-1023 K were -6.75 x 10(-6) K-1 for S-1, -12.91 x 10(-6) K-1 for FeS-1, -16.02 x 10(-6) K-1 for TS-1 and -17.92 x 10(-6) K-1 for ZrS-1. The highest lattice thermal expansion coefficients (alpha(v)) obtained were -11.53 x 10(-6) K-1 for FeS-1 in temperature range 298-1173 K, -20.86 x 10(-6) K-1 for TS-1 and -25.54 x 10(-6) K-1 for ZrS-1, respectively, in the temperature range 298-1623 K. Tetravalent cation substitution for Si4+ in the lattice leads to a high thermal stability as compared to substitution by trivalent cations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; Thermal expansion; X-ray diffraction